First detection of a lizard-associated papillomavirus in the splendid japalure (Japalura splendida) from southwestern China - Tian, Zhige; Li, Tingjie; Fan, Yuping; Li, Jiayi; Luo, Sirong; Cao, Wanxin; Pan, Qing; Hu, Xiaoliang (Frontiers in Microbiology, 2025)
IntroductionPapillomaviruses have been previously identified in mammals, avians and fish. However, few numbers of reptiles’ PVs have been characterized.MethodsThis study investigated the oral cavity of the splendid japalure (Japalura splendida) in southwestern China using high-throughput sequencing. The presence of papillomavirus strain JsPV in oral samples was confirmed using PCR with consensus primers.Results and discussionIn this study, a papillomavirus strain, designated JsPV, in the oral cavity of the splendid japalure (Japalura splendida) in southwestern China. The complete JsPV genome was sequenced, comprising  222 bp. Phylogenetic analysis based on the L1 protein revealed that JsPV clustered closely with gecko-derived strains (HfrePV1 and HfrePV2) and other sauropsid-associated papillomaviruses, while remaining distinct from mammalian- and fish-associated lineages. These findings provide insights into the evolutionary origins of papillomaviruses in reptiles.